“Living” Radical Polymerization in Tubular Reactors, 2 - Process Optimization for Tailor-Made Molecular Weight Distributions - Asteasuain, Mariano (2008)
Living radical polymerization is a relatively new polymerization process that can be used for preparation of resins with controlled structure. In this work, a mathematical model developed previously to describe nitroxide-mediated living radical polymerizations performed in tubular reactors is used for the optimization of the process and obtainment of tailor-made MWDs. Operating conditions and design variables are determined with the help of optimization procedures in order to produce polymers with specified MWD. It is shown that bimodal and trimodal MWDs, with given peak locations, can be obtained through proper manipulation of the operating conditions. This indicates that the technique discussed in this work is suitable for detailed design of the MWD of the final polymer.